Strategi Personal Selling dan Citra Perusahaan: Penggerak Keputusan Menabung Modern - Alfianto , Andi Alfianto; Alimuddin, Firman (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
the purpose of this research is to determine the influence of personal selling and company image on saving decisions at BANK MANDIRI Pinrang Branch. To find out how Personal Selling and Company Image simultaneously influence Saving Decisions at BANK MANDIRI Pinrang Branch. The method used in this research is quantitative with a descriptive approach. Samples were obtained using a purposive sampling technique. The data testing technique was carried out by testing validity and reliability using the SPSS. for Windows 26 program. Meanwhile, the data processed was primary data sourced from the results of questionnaires filled in by respondents. The research results show that partial purchasing power influences purchasing decisions with a value of tcount>ttable, namely (3.117>1.984), and the significance is smaller than 5% (0.002<0.050). Product quality has a partial effect on purchasing decisions with the tcount>ttable value, namely (7.475>1.984) and, the significance is less than 5% (0.000<0.050). Simultaneously, the variables purchasing power and product quality influence buying decisions with a value of fcount>ftable, namely (154,384>3.09) and a significance that is smaller than 0.05 (0.000<0.05).